Temperature and pH Profiling of Extracellular Amylase from Antarctic and Arctic Soil Microfungi - Krishnan, Abiramy; Alias, Zazali; Convey, Peter; González-Aravena, Marcelo; Smykla, Jerzy; Rizman Idid, Mohammed; Alias, Siti Aisyah (Fermentation, 2022)
While diversity studies and screening for enzyme activities are important elements of understanding fungal roles in the soil ecosystem, extracting and purifying the target enzyme from the fungal cellular system is also required to characterize the enzyme. This is, in particular, necessary before developing the enzyme for industrial-scale production. In the present study, partially purified α-amylase was obtained from strains of Pseudogymnoascus sp. obtained from Antarctic and Arctic locations. Partially purified α-amylases from these polar fungi exhibited very similar characteristics, including being active at 15 °C, although having a small difference in optimum pH. Both fungal taxa are good candidates for the potential application of cold-active enzymes in biotechnological industries, and further purification and characterization steps are now required. The α-amylases from polar fungi are attractive in terms of industrial development because they are active at lower temperatures and acidic pH, thus potentially creating energy and cost savings. Furthermore, they prevent the production of maltulose, which is an undesirable by-product often formed under alkaline conditions. Psychrophilic amylases from the polar Pseudogymnoascus sp. investigated in the present study could provide a valuable future contribution to biotechnological applications.